A Multidisciplinary Evaluation of a Web-based eLearning Training Programme for SAFRON II (TROG 13.01): a Multicentre Randomised Study of Stereotactic Radiotherapy for Lung Metastases. Issue 9 (September 2016) - Pham, D.; Hardcastle, N.; Foroudi, F.; Kron, T.; Bressel, M.; Hilder, B.; Chesson, B.; Oates, R.; Montgomery, R.; Ball, D.; Siva, S.
Abstract: Aims: In technically advanced multicentre clinical trials, participating centres can benefit from a credentialing programme before participating in the trial. Education of staff in participating centres is an important aspect of a successful clinical trial. In the multicentre study of fractionated versus single fraction stereotactic ablative body radiotherapy in lung oligometastases (TROG 13.01), knowledge transfer of stereotactic ablative body radiotherapy techniques to the local multidisciplinary team is intended as part of the credentialing process. In this study, a web-based learning platform was developed to provide education and training for the multidisciplinary trial teams at geographically distinct sites. Materials and methods: A web-based platform using eLearning software consisting of seven training modules was developed. These modules were based on extracranial stereotactic theory covering the following discrete modules: Clinical background; Planning technique and evaluation; Planning optimisation; Four-dimensional computed tomography simulation; Patient-specific quality assurance; Cone beam computed tomography and image guidance; Contouring organs at risk. Radiation oncologists, medical physicists and radiation therapists from hospitals in Australia and New Zealand were invited to participate in this study. Each discipline was enrolled into a subset of modules (core modules) and was evaluated before and after completing each module. The effectiveness of the eLearning training will be evaluated based on (i) knowledge retention after participation in the web-based training and (ii) confidence evaluation after participation in the training. Evaluation consisted of a knowledge test and confidence evaluation using a Likert scale. Results: In total, 130 participants were enrolled into the eLearning programme: 81 radiation therapists (62.3%), 27 medical physicists (20.8%) and 22 radiation oncologists (16.9%). There was an average absolute improvement of 14% in test score ( P < 0.001) after learning. This score improvement compared with initial testing was also observed in the long-term testing (>4 weeks) after completing the modules ( P < 0.001). For most there was significant increase in confidence ( P < 0.001) after completing all the modules. Highlights: 130 participants enrolled into a lung stereotactic ablative body radiotherapy eLearning programme. The eLearning programme consisted of seven training modules covering stereotactic topics. eLearning participation showed a 14% improvement in knowledge based on testing before and after eLearning intervention. For most participants there was a significant ( P < 0.001) improvement in confidence after completing each training module.